2021
DOI: 10.1016/j.envpol.2021.118198
|View full text |Cite
|
Sign up to set email alerts
|

LPG stove and fuel intervention among pregnant women reduce fine particle air pollution exposures in three countries: Pilot results from the HAPIN trial

Abstract: The Household Air Pollution Intervention Network trial is a multi-country study on the effects of a liquefied petroleum gas (LPG) stove and fuel distribution intervention on women's and children's health. There is limited data on exposure reductions achieved by switching from solid to clean cooking fuels in rural settings across multiple countries. As formative research in 2017, we recruited pregnant women and characterized the impact of the intervention on personal exposures and kitchen levels of fine particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“… 18 21 Briefly, IRCs were located in relatively low-density rural areas that had low background air pollution concentrations according to 24- to 48-h ambient outdoor measurements, as well as minimal observation of other pollution sources. 17 , 22 , 23 Study locations were selected in areas where most households typically used traditional biomass stoves to fulfill their cooking and energy needs. Within each IRC, specific study sites were chosen during a 12-month period of formative research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 21 Briefly, IRCs were located in relatively low-density rural areas that had low background air pollution concentrations according to 24- to 48-h ambient outdoor measurements, as well as minimal observation of other pollution sources. 17 , 22 , 23 Study locations were selected in areas where most households typically used traditional biomass stoves to fulfill their cooking and energy needs. Within each IRC, specific study sites were chosen during a 12-month period of formative research.…”
Section: Methodsmentioning
confidence: 99%
“…Intervention components were informed by formative research and described in detail previously. 21 , 22 The stoves and fuel cylinders were procured separately at each IRC following formative research on local cooking practices and equipment availability. Stove design varied by site, but all stoves had at least two burners and included additional components for preparation of traditional foods (e.g., a flat griddle for cooking tortillas in Guatemala and a roasting grill in Rwanda).…”
Section: Methodsmentioning
confidence: 99%
“…The HAP exposure levels associated with biomass use (such as at baseline and in the control arm) in our study are at the lower end of what has been reported in previous trials, with the possible exception of the GRAPHS trial. Based on pilot phase exposure reductions 20,21 and estimated supra-linear E-R relationships for HAP and birthweight, 31 we hypothesised that the levels observed during pilot work implied that exposure reductions would occur on the steep part of the response curve for birthweight. Given the relative paucity of studies on quantitative E-R analyses for HAP based on personal exposures, it is quite possible that the shape of the E-R curve is different than what was previously estimated.…”
Section: Discussionmentioning
confidence: 99%
“…HAPIN was designed to be a proof-of-concept, efficacy trial. Indeed, the investigators conducted at least 18 months of formative field research [ 20 , 21 , 22 , 23 , 24 ] or leveraged ongoing research [ 25 ] to identify study settings with low population density and low ambient air pollution. Formative activities included training personnel in ultrasound measurements to assess gestational period that met eligibility criteria [ 26 ], developing procedures for stove installation and training in stove use [ 10 ], assessing methods of fuel delivery to assure a continuous fuel supply, developing and implementing behavioral messages for intervention adherence, including monitoring temperature of biomass fuel stoves in intervention homes [ 13 ] and collecting outcome data within specific time windows [ 10 ].…”
Section: Discussionmentioning
confidence: 99%